Implementation of jute-based nose holder in surgical masks to reduce plastic contamination - Md. Ehsanur Rashid; Raihan Ul Haque; Md. Rubel Khan; Md. Bashar Uddin; Zahidul Islam Khan; Md Atikul Islam; Towfik Aziz Kanon; Md. Washique Tonmoy (Heliyon, 2023)
Plastic, in all its forms, always harms the environment, humans, and other living organisms. The coronavirus situation exacerbates the use of plastic products more than at any other time, of which surgical masks contribute to plastic pollution the most. These masks spread to terrestrial and aquatic environments, where they break down into even more noxious microplastics. These microplastics enter the human food chain through water and fish, causing severe damage to the lungs, kidneys, and intestines and even causing death. In this paper, a jute nose holder mask was prepared as an alternative to typical masks to reduce plastic pollution. The jute nose holder was produced with a modified jute flyer-spinning frame machine, where jute was used as the sheath and metal wire was applied as the core component. The nose holder was later coated with starch-based natural gum. Then, the non-woven fabric of 75 grams per square meter (GSM), and the jute nose holder were used to produce the alternative, environmentally friendly mask, which might reduce the 773 tons of plastic waste generated daily from the nose holder of the mask. This alternative mask was then distributed to 900 people for a survey to find out their opinion. From the results of the survey, it is seen that 82.6% of people felt no problem in the nose when they put on the given mask. 85.6% considered the mask more comfortable than the traditional mask, and it was rated above average by 79.8% of the surveyors. So, this study suggests that the given mask can be a sustainable alternative to traditional masks.